Emerging role of endogenous peptides encoded by non-coding RNAs in cancer biology - Anna Lucia Tornesello; Andrea Cerasuolo; Noemy Starita; Sara Amiranda; Tiziana Pecchillo Cimmino; Patrizia Bonelli; Franca Maria Tuccillo; Franco Maria Buonaguro; Luigi Buonaguro; Maria Lina Tornesello (Non-coding RNA Research, 2025)
Non-coding RNAs have long been recognized for their regulatory roles in various cellular processes, including cancer development and progression. Recent advancements have shed light on a novel aspect of non-coding RNA biology, revealing their ability to encode endogenous peptides also named micropeptides or microprotein through short open reading frames (sORFs). These small proteins play crucial roles in oncogenic processes, acting as either tumour suppressors or tumour promoters, and hold enormous potential as biomarkers for early diagnosis of cancer and as therapeutic targets. This comprehensive review highlights the state of the art on peptides encoded by long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), elucidating their regulatory functions and implications in different cancer types, including breast cancer, hepatocellular carcinoma and colorectal cancer. The review also discusses challenges and future directions in the exploration of these emerging players in cancer biology, emphasizing the importance of further investigation for their clinical translation in diagnosis and therapy.